Renhed, ritual og samfund hos Mary Douglas - Aktor, Mikael (Religionsvidenskabeligt Tidsskrift, 1997)
<span style="font-size: 9pt; font-family: "Times New Roman","serif"; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Shruti; mso-fareast-language: DA; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">“Purity, Ritual and Society According to Mary Douglas: A problematization inspired by some recent post-structuralist critiques”. Mary Douglas’ two pioneering books, Purity and Danger and Natural Symbols, were together a major break-through in the study of religions. Today, when post-structuralist voices are heard more and more clearly, also in this discipline, it is, however, time for a rethinking of her hypotheses. The present article attempts particularly to account for two such critiques. One is the objection against the linguistic paradigm and specially against its separation between thought and act, meaning and ritual. On the basis of the criticisms of Talal Asad, Catherine Bell and others (and referring back to philosophy of language) purity is instead seen as a felicity condition of ritual action, practice or agency. The other critique is based on phenomenology of perception and is directed at the fundamental distinction in Douglas’ social symbolism between an undifferentiated experience and a conceptual ordering. This distinction is a misrepresentation of Gestalt psychology according to Ariel Glucklich who, instead, develops a phenomenological definition of purity as ‘resonance’ between the ritual’s mythical narrative and the sensory experience of its performance.